PENGARUH LEVERAGE, UMUR PERUSAHAAN, PROFITABILITAS, FIRM SIZE, AUDIT FIRM SIZE TERHADAP VOLUNTARY DISCLOSURE - Fahma Dewi Firmaningtyas; Dinda Amelia Kusumastuti (INVENTORY: JURNAL AKUNTANSI, 2019)
Changes in economic conditions affect the business world, therefore companies must be more transparent in disclosing company information. The limitation of this research problem is the scope of information including Voluntary Disclosure while the information presented is leverage, age of the company, profitability, firm size and audit firm size. This study tries to analyze the determinants of the level of voluntary disclosure companies in BEI Manufacturing companies in 2015-2017. For this purpose the disclosure data is 65 data from BEI Manufacturing companies in 2015-2017, companies are selected and analyzed using multiple Linear regression. This study shows that the relationship of exogenous company level factors including profitability, firm size, audit firm size, company age and leverage on the voluntary disclosure index. The results of this study indicate that leverage, age of the company, Firm Size and Audit Firm size affect the area of voluntary disclosure or Voluntary Disclosure. While profitability has no effect on the area of Voluntary Disclosure disclosure.Keywords: Voluntary Disclosure, profitability, company size, Audit Firm size, company age and leverage